2023
DOI: 10.1159/000529588
|View full text |Cite
|
Sign up to set email alerts
|

Serum Potassium Trajectory during Acute Kidney Injury and Mortality Risk

Abstract: Background: The association between potassium (sK) level trajectory and mortality or the need for kidney replacement therapy (KRT) during acute kidney injury (AKI) has not been adequately explored. Methods: In this prospective cohort, AKI patients admitted to the Hospital Civil de Guadalajara were enrolled. Eight groups based on the sK (mEq/L) level trajectories during 10 days of hospitalization were created, (1) normokalemia (normoK), defined as sK between 3.5-5.5; (2) hyperkalemia to normoK; (3) hypokalemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(58 reference statements)
1
0
0
Order By: Relevance
“…Differences between prescribed and offered KRT doses have been previously described, and it is well known that subdoses of KRT are associated with higher lethality [33][34][35]. Indeed, our study showed that the achievement of adequate markers of efficient KRT was associated with reduced lethality rates in both pandemic waves, especially with regard to serum potassium levels [36]. The decreased efficiency of KRT observed during the second wave might be attributed to several factors.…”
Section: Plos Onesupporting
confidence: 60%
“…Differences between prescribed and offered KRT doses have been previously described, and it is well known that subdoses of KRT are associated with higher lethality [33][34][35]. Indeed, our study showed that the achievement of adequate markers of efficient KRT was associated with reduced lethality rates in both pandemic waves, especially with regard to serum potassium levels [36]. The decreased efficiency of KRT observed during the second wave might be attributed to several factors.…”
Section: Plos Onesupporting
confidence: 60%